Database for the kinetics of the gas-phase atmospheric reactions of organic compounds - M. R. McGillen; M. R. McGillen; W. P. L. Carter; A. Mellouki; J. J. Orlando; B. Picquet-Varrault; T. J. Wallington (Earth System Science Data, 2020)
We present a digital, freely available, searchable, and evaluated compilation of rate coefficients for the gas-phase reactions of organic compounds with OH, Cl, and NO3 radicals and with O3. Although other compilations of many of these data exist, many are out of date, most have limited scope, and all are difficult to search and to load completely into a digitized form. This compilation uses results of previous reviews, though many recommendations are updated to incorporate new or omitted data or address errors, and includes recommendations on many reactions that have not been reviewed previously. The database, which incorporates over 50 years of measurements, consists of a total of 2765 recommended bimolecular rate coefficients for the reactions of 1357 organic substances with OH, 709 with Cl, 310 with O3, and 389 with NO3, and is much larger than previous compilations. Many compound types are present in this database, including naturally occurring chemicals formed in or emitted to the atmosphere and anthropogenic compounds such as halocarbons and their degradation products. Recommendations are made for rate coefficients at 298 K and, where possible, the temperature dependences over the entire range of the available data. The primary motivation behind this project has been to provide a large and thoroughly evaluated training dataset for the development of structure–activity relationships (SARs), whose reliability depends fundamentally upon the availability of high-quality experimental data. However, there are other potential applications of this work, such as research related to atmospheric lifetimes and fates of organic compounds, or modelling gas-phase reactions of organics in various environments. This database is freely accessible at https://doi.org/10.25326/36 (McGillen et al., 2019).